Resonant tunnelling optoelectronic circuits - Figueiredo, J. M. L. (2012)
We introduce and report recent developments on a novel five port optoelectronic voltage controlled oscillato r consisting of a resonant tunneling diode (RTD) optical-waveguide integrated with a laser diode. The RTD-based optoelectronic oscillator (OEO) has both optical and electrical input and output ports, with the fifth port allowing volta ge control. The RTD-OEO locks to ref- erence radio-frequency (RF) sources by either optical or electrical injection locking techniques allowing remote sync hronization, eliminating the need of impedance matching between traditional RF oscillators. RTD-OEO functions include generation, amplification and distribution of RF carriers, clock recov- ery, carrier recovery, modulation and demodulation and frequency synthesis. Self-injection locking operation modes, where small portions of the output elec- trical/optical signals are fed back into the electrical/optical input ports, are also proposed. The self-phase locked loop configuration can give rise to low-noise high-stable oscillations, not limited by the RF source performance and with no need of external optoelectronic conversion.